2022
DOI: 10.1002/btm2.10322
|View full text |Cite
|
Sign up to set email alerts
|

Sound‐guided assessment and localization of pulmonary air leak

Abstract: Pulmonary air leak is the most common complication of lung surgery, with air leaks that persist longer than 5 days representing a major source of post‐surgery morbidity. Clinical management of air leaks is challenging due to limited methods to precisely locate and assess leaks. Here, we present a sound‐guided methodology that enables rapid quantitative assessment and precise localization of air leaks by analyzing the distinct sounds generated as the air escapes through defective lung tissue. Air leaks often pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…We also performed a sound‐based air leak detection test established by our group, wherein the intensity and frequency of air leak sounds were analyzed to quantify severity of air leak. [ 69 ] We found that after induction of air leak, sound pressure levels were significantly elevated relative to baseline (baseline: 7.86 ± 0.11 dBA, air leak: 49.4 ± 20.8 dBA, p < 0.05). After sealant application; however, sound pressure levels showed no significant difference compared to baseline levels (sealant: 10.2 ± 3.0 dBA, p = 0.893) (Figure 6F).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We also performed a sound‐based air leak detection test established by our group, wherein the intensity and frequency of air leak sounds were analyzed to quantify severity of air leak. [ 69 ] We found that after induction of air leak, sound pressure levels were significantly elevated relative to baseline (baseline: 7.86 ± 0.11 dBA, air leak: 49.4 ± 20.8 dBA, p < 0.05). After sealant application; however, sound pressure levels showed no significant difference compared to baseline levels (sealant: 10.2 ± 3.0 dBA, p = 0.893) (Figure 6F).…”
Section: Resultsmentioning
confidence: 84%
“…Quantitative Sound Analysis: Quantitative sound analysis algorithms were used to detect presence or absence of air leak in swine lungs, as previously described. [69] Measurements were performed at baseline, after air leak induction, and after sealant application, and analyzed using Audacity and custom MATLAB code. Values were averaged across three breaths.…”
Section: Methodsmentioning
confidence: 99%